Prognostic impact of the inclusion of uPA/PAI-1 tumor levels in the current adjuvant treatment decision-making for early breast cancer. (February 2014) - Saadoun, Haïdar; Lamy, Pierre-Jean; Thezenas, Simon; Pouderoux, Stéphane; Bibeau, Frédéric; Montels, Frédéric; Romieu, Gilles; Colombo, Pierre-Emmanuel; Gutowski, Marian; Jacot, William
ABSTRACT Aims: Following the introduction of new adjuvant therapies we wanted to reappraise the prognostic and predictive value of uPA/PAI-1 in early breast cancer.Patients & methods: This monocentric retrospective study included 652 patients who had curative surgery between 2006 and 2011 and adjuvant treatment decision-making, taking into account uPA/PAI-1 tumor levels.Results: uPA and PAI-1 levels were associated with classical clinicopathological parameters and adjuvant chemotherapy decision, but not with peritumoral vascular invasion (PVI; also known as peritumoral vascular emboli). HER2 overexpression, PVI and uPA/PAI-1 levels were not significantly associated with relapse-free survival in univariate analysis. In multivariate analysis, T stage, N stage and progesterone receptors were the only independent relapse-free survival predictive factors.Conclusion: The absence of an association between uPA/PAI-1 and PVI allows their concomitant consideration in adjuvant treatment discussion. The overall good prognosis of patients with high uPA/PAI-1 levels might be linked to the uPA/PAI-1 predictive value and the inclusion of these parameters in adjuvant guidelines.